2021
DOI: 10.1177/20503121211049121
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of childhood autism among nurses working in governmental hospitals of Addis Ababa, Ethiopia

Abstract: Introduction: Autism is a neurodevelopmental disorder that occurs in the early childhood period and is characterized by altered social interaction, communication problems, repetitive, and stereotyped behavior. Genetic, environmental, or physical risk factors are associated with prenatal, natal, or postnatal complications, leading to the development of autism spectrum disorders. Prompt diagnosis and management should be an integral component of the care provision in countries like Ethiopia. Objective: This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…On average participants responded 50% of total scores obtainable which is lower than results from Nigeria where participants correctly answered 67.9% of total scores obtainable (19). A higher proportion of nurses (54.35%) working in governmental hospitals in Addis Ababa demonstrated good knowledge about ASD compared to the teachers in this study (14).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…On average participants responded 50% of total scores obtainable which is lower than results from Nigeria where participants correctly answered 67.9% of total scores obtainable (19). A higher proportion of nurses (54.35%) working in governmental hospitals in Addis Ababa demonstrated good knowledge about ASD compared to the teachers in this study (14).…”
Section: Discussionmentioning
confidence: 45%
“…In Ethiopia, a study was conducted to assess the knowledge among nurses working in governmental hospitals in Addis Ababa, and the ndings indicated that nurses had a good level of knowledge about ASD (14). Previous researches, done in Addis Ababa, has examined the learning di culties experienced by children with autism and the challenges encountered in teaching processes within autism centers.…”
Section: Introductionmentioning
confidence: 99%
“…The most described CAMH disorder was autism, which was reported in ten papers [ 33 , 39 , 40 , 57 , 58 , 60 , 62 – 64 , 68 ], papers described CAMH in general [ 27 , 28 , 35 , 43 ], one reported on child and adolescent mental illness [ 41 ], two reported on developmental disorders [ 22 , 67 ], one on child mental health [ 59 ], one on adolescent depression [ 65 ], one on Tourette’s Syndrome [ 66 ], and one on psychomotor development of children [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the unique experiences of families by health care providers may result in the creation of awareness strategies or programs aimed at empowering parents or caregivers, and in that process boost their self‐esteem, self‐efficacy, adequacy, and ability to control and manage stressful situations due to the ASD diagnosis (Shattnawi et al, 2021). Through the uncovering of family experiences, the authors identified the knowledge gap of education and healthcare professionals regarding the teaching and treatment of children with ASD as they should be prepared and positioned to educate families and siblings on the various aspects of ASD (Tasew et al, 2021; Winslow, 2017). Furthermore, the need for effective collaboration between the health sector and other sectors, particularly education, employment, and social welfare were identified as well.…”
Section: Implications For Healthcare Practice Education and Researchmentioning
confidence: 99%